DINAMIKA PSIKOLOGIS PELAKU SELF-INJURY (STUDI KASUS PADA WANITA DEWASA AWAL) - Ria Kurniawaty (Journal of Research and Measurement in Psychology, 2012)
ABSTRACT This study aimed to gain insight about the dynamics of self-Injury actors. The approach used in this research is a qualitative approach with case study method. Subjects in this study is that two actors Injury non suicidal self-injury self-moderate. Data collection techniques used were observation and interviews. Data analysis using qualitative data analysis techniques and examination techniques data using triangulation. Triangulation is used in this study is the triangulation of methods and sources. This study shows that the psychological dynamics of self-Injury actors in subject 1 came from the family, parenting adopted in the family persuasive. The role of each member of the family is not running as it should. Circumstances are not good parents is what makes the subject to self-injury. Lack of attention and affection from parents makes the subject perform actions that are not controlled by it as self-injury. Subject 2 showed that the role of the family is quite influential for him. Parenting is applied by the subject's father was so protective that makes the subject very often want to feel free. This event makes the subject feel guilty and depressed. Taste is exactly what makes the subject matter that is not doing well coping with self-injury. Keywords: Self-Injury, Psychological Dynamics.